2014
DOI: 10.7883/yoken.67.1
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Survey of Severe Fever with Thrombocytopenia Syndrome Virus Infection of Domestic Animals in Laizhou City, Shandong Province, China

Abstract: SUMMARY:A serosurvey of severe fever with thrombocytopenia syndrome virus (SFTSV) infection in domestic animals was conducted in the rural areas of Laizhou City, Shandong Province, China to determine strategies for control and prevention of SFTS. Serum samples were collected from cattle, goats, dogs, pigs, and chickens and antibodies against SFTSV were detected by double-antigen sandwich enzyme-linked immunosorbent assay (ELISA). Of 641 serum samples, the SFTSV seropositive rate was 41.8z (268/641): 74.8z, 57.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 6 publications
(3 reference statements)
0
42
0
Order By: Relevance
“…This phenomenon indicated that ticks are most likely to be the vector of SFTSV [1, 4, 12]. Most patients were admitted to hospital from May to October.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon indicated that ticks are most likely to be the vector of SFTSV [1, 4, 12]. Most patients were admitted to hospital from May to October.…”
Section: Discussionmentioning
confidence: 99%
“…However, the host range of the virus and the role of these animals in the transmission of SFTSV is poorly understood. [11, 12]. In addition, person to person transmission by contacting with infected patient’s blood or mucous has been reported in China [1315].…”
Section: Introductionmentioning
confidence: 99%
“…* indicates Fisher exact. against SFTSV has been observed in dogs, cattle, and other domestic animals in villages where the patients lived 1,[16][17][18] . The differences in the rates of SFTSV infections among various animal species and regions were statistically significant.…”
Section: Discussionmentioning
confidence: 99%